Upaya Meningkatkan Hasil Belajar Peserta Didik Materi Manusia Makhluk Pribadi Metode Problem Based Learning (Pbl) Pada Kelas X Smkn 1 Tanah Siang - Pangabean Pangabean (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education is important at every level and even determines the quality of further education, and is an integral part of the entire national education system. To improve the quality of education, the government has announced 12 years of basic education, 6 years at the elementary school level, 3 years at the junior high school level and 3 years at the senior high school level. Vocational Secondary Education, provides / prepares basic provisions for students to be able to develop to continue to a higher level, implement real life in society and in the world of work. With this provision, it is hoped that children will be able to realize themselves as individuals, members of society, citizens and members of humanity in developing life around them. In implementing the Merdeka curriculum there are Dimensions and Elements of the Pancasila Student Profile that must be developed, then the Pancasila Student Profile has 6 dimensions and several elements in them: Have faith, fear God Almighty, and have a noble character, Global Diversity, Independent, Work together, Critical reasoning and, Creative. Based on the things found during the learning process, the following conclusions are drawn: The Problem Based Learning (PBL) learning method is a learning method that can improve student learning outcomes to solve the problems they face. By using the Problem Based Learning method, it can improve the learning outcomes of students in each cycle experiencing changes and improvements. This is proven by the achievement of pre-cycle test results with an average percentage of only 72.5% in cycle I, and at the end of cycle II it reached 86.66%, an increase of 14.16%. The application of the PBL Problem Based Learning method can improve the learning outcomes of class X students of SMKN 1 Tanah Siang.